Pelatihan Penggunaan Mikroskop Cahaya bagi Mahasiswa Pendidikan Biologi FKIP ULM dengan Menggunakan Preparat Segar - Nurtamara, Luthfiana; Amintarti, Sri; Ajizah, Aulia; Irianti, Riya; Widiyastuti , Dewi Amelia (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
Microscopes in learning biology are very important as a tool for students in studying microscopic organisms and objects that cannot be seen by the eye directly. The results of the needs analysis show that biology education students in the Year of 2022 have never received training in the use and maintenance of microscopes and have never used a microscope with a magnification of 1000x. therefore, 98% of the survey results to participants indicate the need for training in the use of microscopes. The training on the use of light microscope was trained to make wet mount preparations of Rhoeo discolor leaf stomata and Hibiscus rosa-sinensis flower pollen. The microscopes used were monocular microscope and electric binocular microscope. The microscope magnifications used were 10x10; 10x40; and 10x100. The training results show that students are able to use all microscope magnifications and figures of the results of microscope observations well and clearly. The results of the microscope proficiency test were 21.06%, very good; 45.61% good/adequate grades; 24.56 adequate grades, but there were 8.7% still getting poor grades. The next service can be trained in making preparations with the whole mount preparation method, squash method for mitosis observation, slice preparation method without embedding and slice preparation method with paraffin method.